Development and validation of a professionalism assessment scale for medical students - Klemenc-Ketis, Zalika (Int J Med Educ, 2014)
OBJECTIVES: To develop and validate a scale for the assess-ment of professionalism in medical students based on students' perceptions of and attitudes towards professional-ism in medicine. METHODS: This was a mixed methods study with under-graduate medical students. Two focus groups were carried out with 12 students, followed by a transcript analysis (grounded theory method with open coding). Then, a 3-round Delphi with 20 family medicine experts was carried out. A psychometric assessment of the scale was performed with a group of 449 students. The items of the Professional-ism Assessment Scale could be answered on a five-point Likert scale. RESULTS: After the focus groups, the first version of the PAS consisted of 56 items and after the Delphi study, 30 items remained. The final sample for quantitative study consisted of 122 students (27.2% response rate). There were 95 (77.9%) female students in the sample. The mean age of the sample was 22.1 ± 2.1 years. After the principal component analysis, we removed 8 items and produced the final version of the PAS (22 items). The Cronbach's alpha of the scale was 0.88. Factor analysis revealed three factors: empathy and humanism, professional relationships and development and responsibility. CONCLUSIONS: The new Professionalism Assessment Scale proved to be valid and reliable. It can be used for the assessment of professionalism in undergraduate medical students.